Assessing Knowledge Management Readiness in Higher Education: An Institutional Self-Assessment from Gorontalo, Indonesia - Katili, Muhammad Rifai; Lahay, Sri Nilawaty (Jambura Journal of Informatics, 2026)
Knowledge management (KM) has been widely recognized as a strategic enabler for organizational performance and information systems development, yet its systematic adoption in higher education institutions (HEIs) remains limited, particularly in Indonesia. This study presents an institutional KM readiness assessment at two universities in Gorontalo Province, Universitas Negeri Gorontalo (UNG, public) and Universitas Ichsan Gorontalo (UNISAN, private), as an initial descriptive baseline in this regional context. A quantitative descriptive survey was conducted using an instrument grounded in the Knowledge Management Critical Success Factors (KMCSF) framework, covering three aspects: Abstract (conceptual awareness), Soft (human and organizational factors), and Hard (technology and infrastructure). Data were collected from 226 respondents through purposive sampling. The study aims to assess KM readiness levels at both institutions and compare readiness profiles across the three aspects to identify strengths and priority areas for IS-informed governance improvement. Validity and reliability of the instrument were confirmed on this study's data prior to main data collection. Readiness levels were interpreted using a five-level readiness scale, where classifications reflect overall average scores across all dimensions. Results indicated that UNISAN obtained a score corresponding to Level 4 (Receptive) while UNG obtained Level 5 (Optimal), with both institutions showing relative strengths in technology infrastructure and organizational structure. However, knowledge hub and centers, explicit knowledge management, and organizational culture emerged as shared areas requiring priority attention. These findings establish a descriptive KM readiness baseline for HEIs in Gorontalo Province and offer evidence-based directions for knowledge management system design and IS governance improvement.